State Policies and Islamic Law Regarding Juvenile Punishment for Theft - Suhendar, Suhendar; Yunus, Nur Rohim; Rezki, Annissa (Islamic Criminal Law Study Program, Faculty of Sharia and Law, Sunan Ampel State Islamic University Surabaya, Surabaya, East Java, Indonesia., 2023)
The development of an increasingly sophisticated era certainly has an impact on children, both positive and negative impacts. Due to the absence of maximum direction and assistance to children, children can at any time do disgraceful acts. When children are involved in the crime of theft, they will be faced with the law and processed. Therefore, there is a need for special guidance and assistance from parents and parties whose status and roles have been recognized as external companions for these children. In this research, the writer uses descriptive qualitative research method with normative juridical research type. The analysis was conducted to determine the form of state and Islamic protection against children who are perpetrators of the crime of theft. The results of the study state that the judge can give a decision on the case of a child crime case of theft. However, legal protection is needed for children who do not commit the crime of theft, considering that they are still underage and still need to be given more maximum attention and guidance. The state protects children because their future is also the future of the state. Every level of society in Indonesia is obligated to provide moral support and guarantee that children in dispute with the law are not excluded from the social environment and society, and that they continue to obtain an appropriate education so that their futures are secure. So that youngsters affected by this law do not feel alienated, continued enjoyment of the nation's youth is possible.